Kajian Teknis Dan Manajerial Pengelolaan Sampah dan Kaitannya Dengan Kesehatan Lingkungan Di Kota Jayapura - Rantetoding, Rosa; Setiani, Onny; Raharjo, Mursid (Jurnal Kesehatan Lingkungan Indonesia, 2006)
ABSTRACK Backround : The waste management in Jayapura is considered poor, since it is still depend on the employees from Sanitation Department and waste container trucks from the Sanitation Department. The other problem is no strict federal regulation and punishment for throwing garbage in inappropriate places. Additionally, the locals forced the government to shut down the Nafri’s solid waste disposal area by holding a demonstration protest because it was not well treated by the government. The objective of this research was to evaluate the technical and management aspect of solid waste management in Jayapura. Methods : This was a description explorative research with qualitative analysis. A laboratory examination has been done in order to find out the quality of river water, wells, and the air condition around the solid waste disposal. Conclusions : There were several aspects which need to be fixed for the solid waste processing in Jayapura. It was Technical Operational, Institution, Finance, Regulation, and the society participation. The solid waste disposal sanitation showed an amount of vector, in this case, is a quite big number of flies that reaches until ninety eight flies per grill block. The quality of clean water in the area around the solid waste disposal and the Nafri’s camp area showed no pollution of heavy metals. However, based on microbiologic examination, the water has not fulfilled the standard quality parameter of bacteriologic. Additionally, the quality of the air is also under the air standard regulation. Keywords : Technical Operation, Waste Management, Environmental Sanitation